An Axiological Analysis Of The Relationship Between Gender-Based Violence And Human Dignity (Zien Journal of Social Sciences and Humanities, 2026)
The article offers an axiological analysis of the relationship between gender-based violence and human dignity. Its central thesis is that gender-based violence is not only a legal offence or a private conflict, but a value-destructive social practice: it transforms the person from an autonomous moral subject into an object of control, fear, humiliation, or dependency. The study relies on Uzbek and CIS scholarship in axiology, gender studies, legal studies, and social psychology, including the works of Q. Nazarov, D. B. Vafaeva, L. R. Shayusupova and I. R. Alizhonov, K. Aliyeva, G. A. Ishankhanova, M. A. Laktionova, S. E. Retsya and Z. V. Lukovtseva, and D. L. Faizova. The empirical and normative context is framed by Uzbekistan's 2019 laws on protection from harassment and violence and equal rights, the Gender Equality Strategy until 2030, and the 2023 amendments that introduced Article 126-1 on domestic violence. Using axiological-hermeneutic, comparative-legal, and qualitative synthesis methods, the article identifies four findings: dignity functions as the highest value criterion in evaluating violence; gender violence reproduces a hierarchy of unequal worth; local institutions such as the mahalla can either normalize harm or become channels of dignity-centered protection; and effective prevention requires harmonizing legal liability with value education, survivor-centered services, and transformation of gender stereotypes. The article concludes that a society that places inson qadri, human worth, at the center of reform must treat gender-based violence as a direct violation of the moral foundations of social life